Integrating Urinalysis Practicum in Science Education: A Descriptive Study of Urine Characteristics and Its Implications for Students’ Conceptual Understanding - Wardah Fitriyani (PT. Komunitas Peneliti Alinea, 2026)
Science education is frequently associated with abstract concepts, thereby necessitating the integration of scientific activities to facilitate students’ conceptual understanding. One such activity is the urine content analysis practicum. Urinalysis is conducted by examining the physical and chemical characteristics of urine to support disease diagnosis and to determine normal physiological conditions. Observations typically include changes in color, odor, and specific chemical reactions. This study aims to determine urine pH, detect the presence of ammonia, and identify the existence of glucose, protein, and bile pigments. A descriptive observational method was employed, involving direct examination of urine samples using various chemical reagents. The findings indicate that normal urine exhibits a pH of approximately 5, reflecting a slightly acidic nature. The presence of ammonia is characterized by a more pungent odor, particularly after the urine is heated or left to stand. The bile test results were negative, as indicated by the absence of a green ring formation. Furthermore, the Benedict test for glucose showed no significant color change, and the protein test also yielded negative results, confirming the absence of glucose and protein in normal urine.